2010
DOI: 10.1080/13504860903357292
|View full text |Cite
|
Sign up to set email alerts
|

Sato Processes in Default Modelling

Abstract: In reduced form default models, the instantaneous default intensity is the classical modelling object. Survival probabilities are then given by the Laplace transform of the cumulative hazard defined as the integrated intensity process. Instead, recent literature tends to specify the cumulative hazard process directly. Within this framework we present a new model class where cumulative hazards are described by self-similar additive processes, also known as Sato processes. Furthermore, we analyse specifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…As these processes are similar, we consider only the Sato-Gamma assumption in the empirical analysis. As shown in Kokholm and Nicolato (2010), in the Sato-Gamma model it can be demonstrated that …”
Section: The Sato Familymentioning
confidence: 95%
See 4 more Smart Citations
“…As these processes are similar, we consider only the Sato-Gamma assumption in the empirical analysis. As shown in Kokholm and Nicolato (2010), in the Sato-Gamma model it can be demonstrated that …”
Section: The Sato Familymentioning
confidence: 95%
“…Furthermore, as observed by Kokholm and Nicolato (2010), the proposed model has a deterministic intensity process given by the equality…”
Section: The Sato Familymentioning
confidence: 99%
See 3 more Smart Citations